Co-creating places: human participatory dynamics through territorial communication - Duarte Melo, Ana (2021)
Co-creation and participatory experiences of place branding as expressions of more resilient, inclusive and more human societies are at the core of this paper. Based on state-of-the art co-creative territorial communication review, and using a methodological approach of interpretative hermeneutics and case studies, we critically reflect on the implications of these phenomena and their contribution to placemaking. If the benefits of stakeholders’ involvement and co-creative practices in different stages of placemaking may add value to territories and coherence to place brands not offering substantial dispute, the implementation of participatory practices expose pragmatic and ethical issues, enhancing the steering role of the facilitator and the vulnerability of deliberative participatory processes. Nevertheless, co-creative contexts powered by human dynamics seem to provide a fruitful ground to achieve territorial consonance, authentic experiences, sense of belonging and a shared vision of a place essence, central to more involved, more sustainable, and more resilient communities.